Neuroprotective effects of leonurine against oxygen-glucose deprivation by targeting Cx36/CaMKII in PC12 cells. - Jiao Li; Shuang Zhang; Xiaoxi Liu; Deping Han; Jianqin Xu; Yunfei Ma (PLoS ONE, 2018)
Leonurine has been reported to play an important role in ameliorating cognitive dysfunction, inhibiting ischemic stroke, and attenuating perihematomal edema and neuroinflammation in intracerebral hemorrhage. However, the exact mechanism and potential molecular targets of this effect remain unclear. Thus, in this study we investigated the neuroprotective effects of leonurine on hypoxia ischemia injury and explored the underlying mechanisms. An in vitro model of oxygen-glucose deprivation (OGD)-induced PC12 cells was established to mimic ischemic-like conditions. Cell viability, apoptosis, Cx36 and pCaMKII/CaMKII expression levels were evaluated after treatment with leonurine. The Cx36-selective antagonist mefloquine and CaMKII Inhibitor KN-93 were used to investigate the neuroprotective effect of leonurine on and the involvement of Cx36/CaMKII in this process. The results revealed that cell viability decreased and cell apoptosis and the protein expression of Cx36 and pCaMKII/CaMKII increased in the OGD-induced PC12 cells. Leonurine significantly increased cell viability and decreased cell apoptosis and the protein expression of Cx36 and pCaMKII/CaMKII in the OGD-induced PC12 cells. The specific inhibitor of Cx36 and CaMKII displayed similar protective effects. Moreover, the inhibition of Cx36 reduced pCaMKII levels and the ratio of pCaMKII/CaMKII in the OGD-induced PC12 cells, and vice versa. Taken together, these results suggest that leonurine might have a protective effect on OGD-induced PC12 cells through targeting the Cx36/CaMKII pathway. Thus, leonurine appears to have potential as a preventive or therapeutic drug against ischemic-induced neuronal injury.